PENGARUH PENERAPAN SISTEM ADMINISTRASI PERPAJAKAN MODERN DAN KESADARAN WAJIB PAJAK PADA KEPATUHAN WAJIB PAJAK - Astana, Wayan Sugi; Merkusiwati, Ni Ketut Lely Aryani (E-Jurnal Akuntansi; Vol 18 No 1 (2017), 2017)
Application of modern tax administration system which covers the areas of organizational structure, business processes and information technology and communications, human resource management and the implementation of good governance is government's attempt to increase the level of taxpayer compliance. In addition to tax administration system, awareness of the taxpayer is one of the factors that affect the level of tax compliance. The purpose of this study was determine the effect of application of modern tax administration system and awareness of the taxpayer in compliance with individual taxpayer in the Tax Office (KPP) Pratama Gianyar. Respondents in this study as many as 100 individuals taxpayer with accidental sampling technique. Methods of data analysis in this study using multiple linear regression analysis. The conclusion of this study is there is positive effect of the application of modern tax administration system and taxpayer awareness on individual taxpayer compliance in KPP Pratama Gianyar.
Keywords: tax administration, awareness, compliance, taxpayer